Administrative action and procedures in comparative law - De Falco, Vincenzo, 1965- (Comparative public law treatise (Series), 2018)
"The volume concerns the evolution of the main elements of administrative procedures, provides a diachronic reconstruction and bridges a gap in comparative studies that had observed the phenomenon through the prevailing analysis of foreign law. The author analyses the characteristics of the main juridical experiences and identifies the role played by subjective legal positions, the principle of transparency, the participation, the judicial control and the defects of administrative acts in the formation of the rules on procedures. The analysis is carried out through preliminary methodological clarifications and continues with the verification of the strength with which the principles have established themselves in the national, European and international legal systems. In this way it has been possible to discover models of transparency and participation and identify the functions that the duty to give reasons have in the various jurisdictions. The author reconstructs the systems with which the problems of administrative inertia are tackled and resolved and the limits that the individual juridical experiences impose on the discretionary power, up to identify the models of the administrative action and their diffusion in comparative law"--Back cover